2015
DOI: 10.1155/2015/949163
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Erdheim-Chester Disease and Langerhans Cell Histiocytosis Overlap Syndrome

Abstract: A 48-year-old woman with a past medical history of seizures and end-stage renal disease secondary to obstructive uropathy from retroperitoneal fibrosis presented to the emergency department with seizures and altered mental status. A Glasgow Coma Scale of 4 prompted intubation, and she was subsequently admitted to the intensive care unit. Magnetic resonance imaging of the brain performed to elucidate the aetiology of her seizure showed a dural-based mass within the left temporoparietal lobe as well as mass lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…First identified by Jakob Erdheim, an Austrian pathologist, and William Chester, an American cardiologist, in 1930, they referred to it as ‘lipoid granulomatosis’. Dr Ronald Jaffe reported a third case in 1972, naming the condition Erdheim-Chester disease (ECD) 4. The current prevalence of ECD is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First identified by Jakob Erdheim, an Austrian pathologist, and William Chester, an American cardiologist, in 1930, they referred to it as ‘lipoid granulomatosis’. Dr Ronald Jaffe reported a third case in 1972, naming the condition Erdheim-Chester disease (ECD) 4. The current prevalence of ECD is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient has evidence of LCH on histology, accompanied by imaging findings pathognomonic of ECD. Coexistence of both conditions is rare but some cases have been reported 4. It has been suggested that overlap cases typically present with LCH and later progress to ECD 5.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…The concomitant occurrence of two distinct histiocytoses in the same patient is exceptional, but the association of LCH with ECD seems to be the most frequent ( 2 ). Both LCH and ECD share common clinical manifestations, such as CDI, and nearly 20% of patients with ECD also display LCH lesions ( 2 , 3 ). The present patient was first diagnosed with ECD based on the clinical, radiological, and histopathological context.…”
Section: Discussionmentioning
confidence: 99%